Enhancing environmental literacy through project-based edu-tourism in mangrove ecosystems: The influence of student’s initial academic ability - Sucilestari, Ramdhani; Arizona, Kurniawan; Sukardi, Rendi Restiana; Ahmad, Mohd Khairul Azmi bin (Journal of Environment and Sustainability Education, 2025)
This study examines the effectiveness of project-based edu-tourism (PBET) in mangrove ecosystems for enhancing environmental literacy among university students, with particular attention to the role of initial academic ability. A 2×2 factorial design was employed with 75 students from the PGMI Department at UIN Mataram, divided into an experimental group (38 students) participating in a two-week PBET program and a control group (37 students) receiving conventional classroom instruction. Environmental literacy was assessed through pre- and post-test measures, with learning improvement calculated using N-gain scores. The results from factorial ANCOVA revealed that the PBET group achieved significantly higher post-test scores compared to the control group (F(1,70) = 167.344, p < .001), demonstrating the effectiveness of PBET in enhancing environmental literacy. However, initial academic ability was not a significant predictor of environmental literacy outcomes (F(1,70) = 0.098, p = .755), nor was the interaction between class type and initial academic ability significant (F(1,70) = 0.002, p = .961). These findings suggest that PBET is an effective pedagogical approach for improving environmental literacy across diverse academic levels, underscoring its potential for inclusive, experiential learning.